Race, Space, and Violence: Exploring Spatial Dependence in Structural Covariates of White and Black Violent Crime in US Counties - Light, Michael T. (Journal of quantitative criminology, 2012)
Objectives To join the literature on spatial analysis with research testing the racial invariance hypothesis by examining the extent to which claims of racial invariance are sensitive to the spatial dynamics of community structure and crime. Methods Using 1999–2001 county-level arrest data, we employ seemingly unrelated regression models, spatial lag models, and geographically weighted regression analyses to (1) compare the extent of racial similarity/difference across these different modeling procedures, (2) evaluate the impact of spatial dependence on violent crime across racial groups, and (3) explore spatial heterogeneity in associations between macro-structural characteristics and violent crime. Results Results indicate that spatial processes matter, that they are more strongly associated with white than black violent crime, and that accounting for space does not significantly attenuate race-group differences in the relationship between structural characteristics (e.g., structural disadvantage) and violent crime. Additionally, we find evidence of significant variation across space in the relationships between county characteristics and white and black violent crime, suggesting that conclusions of racial invariance/variation are sensitive to where one is looking. These results are robust to different specifications of the dependent variable as well as different units of analysis. Conclusions Our study suggests the racial invariance debate is not yet settled. More importantly, our study has revealed an additional level of complexity—race specific patterns of spatially heterogeneous effects—that future research on social structure and racial differences in violence should incorporate both empirically and theoretically.